The impact of flywheel resistance squat training on lower limb strength in female college basketball players - Xie, Lin; Qu, Wenhao; Dai, Jing; Xu, Jiamin; Zhang, Wenfeng; Sun, Jian; Song, Wenfeng; Li, Duanying (Frontiers in Physiology, 2024)
ObjectiveThis study compared the effects of Flywheel Resistance Squat Training (FRST) vs. Traditional Resistance Squat Training (TRST) on lower body strength in female collegiate basketball players.MethodsNineteen participants were randomly assigned to either the FRST group (n = 9) or the TRST group (n = 10) through a random number draw. Both groups underwent a 6-week intervention with training sessions conducted twice a week. The FRST group utilized an inertia of 0.075 kg ·m2, while another group trained at 80% of their one-repetition maximum (1RM). Each training session consisted of 4 sets of 8 repetitions with a 3-minute rest between sets. Both groups performed standardized warm-ups and stretches before and after each training session. The effectiveness of the training methods was assessed through the Countermovement Jump (CMJ), Reactive Strength Index (RSI), Eccentric Utilization Ratio, Running Vertical Jump, and 1RM squat.ResultsThe FRST and TRST groups showed differences within groups in both CMJ and 1RM squat (p < 0.01), with the FRST group demonstrating moderate effect sizes in CMJ (Hedges’ g = 0.59) and 1RM (Hedges’ g = 1.01). However, there were no differences between groups (p > 0.05). The Eccentric Utilization Ratio showed a small effect size (p = 0.78; ηp2=0.01). Additionally, Reactive Strength Index and Running Vertical Jump exhibited low test-retest reliability.ConclusionThe two groups did not exhibit a statistically significant difference. Nonetheless, both FRST and TRST demonstrated positive effects on 1RM squat and CMJ performance compared to baseline values for each method. Therefore, flywheel resistance training can be considered an effective alternative to traditional resistance training for enhancing strength levels in female basketball players.